BAZI 2-(4H-[1,2,4]TRİAZOL-3-İL-SULFANİL)-ASETAMİT TÜREVLERİNİN ANTİOKSİDAN VE ANTİTÜMÖR ÖZELLİKLERİNİN ARAŞTIRILMASI - DEMİR, SELAHATTİN (Fırat Üniveristesi, 2012)
Bu araştırmada, bazı 2-(4H-[1,2,4]triazol-3-il-sulfanil)-asetamit türevlerinin, lipid peroksidasyonunun derecesini gösteren MDA konsantrasyonu, antioksidan A, E, C vitaminlerinin düzeyleri üzerine olan etkisi ve antitümör özellikleri araştırıldı.Deney grupları arasındaki karşılaştırılmalarda A, E vitaminleri ve MDA konsantrasyonlarının istatistiksel olarak değiştiği gözlendi. Ölçülen parametreler ve deney süresince canlı hücre sayısına bakıldığında bileşiklerin L 1210 hücre tipinde etkili bir sitotoksik aktiviteye sahip olduğu görüldü.Sonuç olarak, ölçülen parametreler bütün maddelerin oksidatif stres oluşturduğunu göstermektedir.

In this research, the in vitro effect of some 2-(4H-[1,2,4]triazole-3-yl-sulfanyl)-acetamide derivative on the MDA concentration which is an indicator of lipid peroxidation, antioxidant vitamins A, E, C levels and antitumour activity in cell culture media were investigated.In the comparison done among groups, it was observed that concentrations of vitamins A, E and MDA were statistically changed. Looking at the measured parameters during the experiment, the number of live cells, the compounds is seen an effective antitumour activity in the L 1210 cell types.In conclusion, the parameters measured here in the show that all compounds caused a considerable oxidative stress.
The investigation of antitumuor and antioxidant properties of some 2-(4h-[1,2,4]triazole-3-yl-sulfanyl)-acetamide derivative
Keywords: Biyokimya